Biocomposite Headrests Design Criteria Weightage: Voice of Stakeholders via Survey and Analytic Hierarchy Process - AZLAN, KHAIRUL AZRI; MANSOR, MUHD RIDZUAN; Mohamad, Effendi; Ito, Teruaki (International Journal of Integrated Engineering, 2026)
This paper presents a novel framework to incorporate the Voice of Stakeholders in evaluating the design criteria for biocomposite headrests through a survey and the Analytic Hierarchy Process (AHP). The framework is meant to complement the sustainable conceptual design framework of biocomposite headrests suggested in the previous study, which is based on the Concurrent Engineering (CE) approach. At first, Product Design Specifications (PDS) for the biocomposite automotive headrest were established, embracing sustainable design practices. Despite the effort towards sustainable design, the voice of pertinent stakeholders should not be disregarded. Therefore, a survey was conducted to identify customers' determined criteria, and mapped to the designer's determined criteria. Subsequently, subject-matter experts (SMEs) from industries and academia were invited for criteria assessment through the AHP pairwise comparison matrix. The results were analyzed through the AHP Microsoft Excel tool with multiple inputs. The criteria weights (CW) determined by SMEs in priority order are safety (45.7%), comfort (16.7%), cost (15.6%), styling (12.5%), and lastly weight (9.5%), with a consistency index (CI) of only 2.8%, indicating a consistent response by SMEs. The SMEs response seems to match customers’ expectations except for the cost, which is focal from the SMEs' point of view. For the criteria global weight (CGW), Factor of Safety (FoS) and maximum Von Misses stress are the most important criteria with an equal value of 22.9%, followed by manufacturability rating with 15.6%, support area with 12.8%, style rating with 12.5%, volume with 9.5%, and finally adjuster rating with 3.8%. The criteria weight will be used by the designer in the concept generation and selection stages. This framework can also be used for other product designs with identical nature, especially automotive components that have direct interaction with occupants.